Graduate Tax Education in AACSB Schools: Where We Stand Today. - Tidwell, Victor H.; Wyndelts, Robert W. (The Accounting Review, 1977)
ABSTRACT: The purposes of the study include: (1) updating the Lubbell/Broden study which appeared in the January 1975, issue of THE ACCOUNTING REVIEW, (2) identifying the AACSB school offering three or more graduate-level tax courses, irrespective of the label on the degree, (3) providing faculty data at schools offering a concentration of tax courses and (4) identifying those schools which interact with a College of Law relative to graduate tax education. The study was conducted by direct mail questionnaire to all AACSB schools in the United States. Conclusions of the study are (1) available concentration in graduate tax courses is growing (2) students, recruiters and faculty need to know which schools are offering what courses and (3) there appears to be a growing need for qualified tax faculty members.